Machine Learning Classification Model to Label Sources Derived from Factor Analysis Receptor Models for Source Apportionment - Vikas Kumar; Vasudev Malyan; Manoranjan Sahu; Basudev Biswal (Aerosol and Air Quality Research)
Abstract Factor analysis (FA) receptor models are widely used for source apportionment (SA) due to their ability to extract the source contribution and profile from the data. However, there is subjectivity in the source identification and labelling due to manual interpretation, which is time-consuming. This raises a barrier to the development of the real-time SA process. In this study, a machine learning (ML) classification algorithm, k-nearest neighbour (kNN), is applied to the source profiles obtained from the United States Environmental Protection Agency’s (U.S. EPA) SPECIATE database to develop a model that can automatically label the factors derived from FA receptor models. The train and test score of the model is 0.85 and 0.79, respectively. The overall weighted average precision, recall and F1 score is 0.79. The performance of the model during validation exhibits acceptable results. The application of ML models for source profile labelling will reduce the time taken and the subjectivity associated with results due to modeler bias. This process can act as another layer of the process for verification of the results of FA receptor models. The application of this methodology advances the process towards real-time SA.